Fundamentals of Entrepreneurship (ENT 300) Business Plan : Barber App Service / Nur Faeqah Syazanie Roslan - Roslan, Nur Faeqah Syazanie (2020)
First of all, Home Barber service is a haircut service that we provide to the customer. The special of this service is we provide a haircut service at customer’s house. By then, people does not have to face the difficulty such as traffic jam to go to the barber shop. We as a middle person collaborate with the service provider to deliver the best service to our customer. This is because there are some barber are not known by people and also who cannot afford to rent a shop. Indirectly, we help service provider to gain customer and we help customer to solve their problem. One of their problem is time constraint.